Saving from unnecessary pancreaticoduodenectomy. Brunner's gland hamartoma: Case report on a rare duodenal lesion and exhaustive literature review. (May 2017) - Peloso, Andrea; Viganò, Jacopo; Vanoli, Alessandro; Dominioni, Tommaso; Zonta, Sandro; Bugada, Dario; Bianchi, Carlo Maria; Calabrese, Francesco; Benzoni, Ilaria; Maestri, Marcello; Dionigi, Paolo; Cobianchi, Lorenzo
Abstract: Introduction: Brunner's gland hamartoma (BGH) is an infrequently encountered, benign, polypoid proliferation of Brunner's glands. Usually these lesions are asymptomatic, just only occasionally presenting with duodenal obstruction or bleeding signs and mimicking a tumoral lesion. Case presentation: A 72-year-old male, referred for recurrent vomiting and epigastralgia, was investigated and all preoperative findings were suggestive of a tumour of the duodenum. During the scheduled pancreaticoduodenectomy a mass, resultant to a polyp, was palpatory felt inside the duodenum and then successfully and completely resected through a duodenotomy avoiding surgical overtreatment and connected postoperative morbidities. Histological analysis showed hyperplasia of Brunner's glands correspondent to a Brunner's gland hamartoma. BGH was undiagnosed before surgery, due to its particular sub-mucosal growth simulating an expanding process starting from the duodenum, and secondly due to unsuccessful biopsies performed during endoscopic procedure. Conclusion: BGH is a rare lesion featuring, when symptomatic, obstructive or bleeding symptoms. Surgical treatment represents the gold standard approach in case of lesions that are technically impossible to remove endoscopically or in case of an undiagnosed lesion. Herein, we report a case of a patient presenting with a duodenal lesion mimicking, in all preoperative findings, a tumour of the duodenum. Duodenotomy and resection of the BGH provided a definitive cure avoiding surgical overtreatment. An intraoperative deep analysis of all surgical cases still remain crucial for a right therapeutic choice even in a new era for surgical technology. For similar intraoperative findings we recommend this technique. Highlights: Brunneroma is an extremely uncommon benign tumour of the duodenum. The case is completely mimicking a malignant tumour of the duodenum. The report is good opportunity to take a stock of the situation from a clinical stand point.